FORMATION OF BASIC COMPETENCIES BASED ON INNOVATIVE APPROACHES IN BIOLOGY TEACHING (International Conference on Modern Science and Scientific Studies, 2025)
The article provides information on the formation of basic competencies based on innovative approaches to teaching biology.